Do financial anxiety and generalized anxiety mediate the effect of perceived organizational support on service employees' career commitment? - Karatepe, Osman M.; Colakoglu, Ulker; Yurcu, Gulseren; Kaya, Sule (Emerald Group Publishing Ltd, 2024)
PurposeThis paper aims to explore financial anxiety and generalized anxiety as the serial mediators linking perceived organizational support (POS) to career commitment. Design/methodology/approachData were collected from 388 managerial and nonmanagerial employees in diverse service areas, such as restaurants, airlines and hotels in Turkey. The direct and mediating effects were tested via the PROCESS macro. FindingsFinancial anxiety partly mediates the impact of POS on career commitment. The findings further reveal that financial anxiety and generalized anxiety serially mediate the effect of POS on career commitment. Practical implicationsManagement should work with mentors to provide employees with psychosocial support during the COVID-19 pandemic. When employees perceive that the firm really cares about them and values their contribution during these challenging days, they display lower anxiety and higher career commitment. Management should also retain employees who are high on career commitment because such employees possess a sense of calling and are unlikely to quit. These implications may not be considered new. However, management would need such employees concerning the firm's performance recovery after COVID-19. Originality/valueWorkers in the service industries suffer from financial and generalized anxieties and display reduced career commitment during COVID-19. However, little is known about the antecedents and outcomes of financial anxiety among hospitality and tourism workers. More importantly, no empirical piece has tested these anxiety variables as the mediators linking POS to career commitment in the pertinent literature so far.
Keywords: Airline staff; Anxiety; Career commitment; Hospitality employees; Perceived organizational support